Deploying an Innovative Routing Algorithm to Enhance Data Security via Internet Protocol Security Measures - Ravikumar, D.; Devi, V.; Sharanya, C.; Vijayalakshmi, P.; Radhakrishnan, P. (Science and Technology - Recent Updates and Future Prospects Vol. 3, 2024)
Internet Protocol Security (IPsec) ensures secure communication between computers by authenticating and encrypting data packets on IP networks, commonly used in virtual private networks (VPNs). IPsec, a network protocol suite, provides authentication and encryption for data packets, enabling secure communication between computers across IP networks, especially in VPNs. Secure your network communication with IPsec, a protocol suite that authenticates and encrypts data packets, essential for establishing secure connections between computers in virtual private networks. IPsec, a protocol suite, safeguards data transmission across IP networks by authenticating and encrypting packets, crucial for ensuring secure communication within virtual private networks. Protect your data transmission on IP networks with IPsec, which offers authentication and encryption for data packets, indispensable for secure communication in virtual private networks. In this proposed work, a secured path of data transmission was provided for better packet transmission between transmitter and receiver. For safe and secure data transmission, an implementation of two routing algorithms has been developed namely Open Shortest Path First and Border Gateway Protocol which are designed for packaging along with switch routing. This embedded algorithm of both OSPF and BGP protocols enhances Internet Protocol security for secure data transmission in the networking domain.